2022
DOI: 10.32598/jpcp.10.1.798.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Group Schema Therapy-based Parenting Education of Mothers on Modifying Maladaptive Schemas of the Child and Improving the Quality of the Parent-Child Relationship

Abstract: Objectives: This study examined the effectiveness of group schema-based parenting education on modifying the child's early maladaptive schemas and improving the quality of the parent-child relationship. Methods: The design of this research is quasi-experimental pretest-posttest with control group. The statistical population of this study includes all mothers and their daughters aged 8 to 10, in District 2 of Tehran, in 1399-1400. Among 65 mothers who announced their readiness to participate in the course by av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…This finding is consistent with previous studies such as Sabzi et al (48) and Khorasanizadeh et al, who showed that parenting is related to early maladaptive schemas (49). As Sabzi et al also stated, the effectiveness of parenting based on schema therapy emphasizes meeting the needs of children to prevent the formation and stabilization of maladaptive schemas (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous studies such as Sabzi et al (48) and Khorasanizadeh et al, who showed that parenting is related to early maladaptive schemas (49). As Sabzi et al also stated, the effectiveness of parenting based on schema therapy emphasizes meeting the needs of children to prevent the formation and stabilization of maladaptive schemas (48).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, through education, parents can help the child's well-being and mental health and empower them. This is why research shows that parent training is an effective tool in changing and directing children's behavior (48,51).…”
Section: Discussionmentioning
confidence: 99%